(untitled) (Applied Biological Research, 2012)
Recently tomato leaf miner, Tuta absoluta, has become one of the most devastating pests of tomato in Egypt, and caused serious damages to tomato production in invaded areas. For this reason, the present study was undertaken to determine the efficacy of 15 insecticides representing different pesticide groups against this insect and also to study their dissipation in tomato fruits. The laboratory experimental results revealed that profenofos, cyfluthrin, lufenuron, chlorpyriphos-methyl and indoxacarb were the most toxic insecticides as compared to other chemicals. These insecticides, 1 day after application, under field conditions caused 84.1 to 73.5% reduction in infestation. With time the bio-residual activity of these compounds gradually decreased with increase in the number of infested fruits. The initial deposits of profenofos, cyfluthrin, lufenuron and chlorpyriphos-methyl ranged from 28.6 to 6.3 ppm, depending on the rate of insecticide application. The loss rate of these amounted to 91.7 to 97.57%, 15 days after treatment. In conclusion, all tested insecticides proved effective against T. absoluta and might be used to control this pest. Further, the bioresidual activity of these compounds did not exceed more than two weeks for the best cases.